Republicanism as a critical idiom : whose, whom against, and what for? - Pehar, Dražen (Array, 2020)
The aim of the paper is to draw briefly the discourse-theoretical foundations to the republican political theory (section 1), with the issue of slave/slavery as a pivotal concern of social and political life (section 2), and then to chart the most interesting consequences for the contemporary versions of the theory as proposed by the key authors (closing paragraphs of section 2, and section 3). the overarching message of the paper reads that republicanism is founded on a specific view of human nature as ens loquens, or zoon logon echon, that has important implications both empirically and normatively. the third, and final, section of the paper enlists six proposals, or suggestions, to contemporary republicans for the purpose of elucidating, first, the limits of republican theory/practice, and second, its intellectual origins as well as its opposition. Sum- marily, the paper lays emphasis as well on the status of republican language as a critical idiom with its pluralist, highly contextualized, and often program- matic/engaged voices.